Design Rancangan User Interface Aplikasi My Pets Dengan Menggunakan Metode Design Thinking - Roni Setyawan; Reski Mai Candra; Eka Pandu Cynthia; Febi Yanto; Muhammad Affandes (JURIKOM (Jurnal Riset Komputer), 2022)
The research was made to produce an application design using the design thinking’s method. The system made on the basis of user interface and user experience. The user interface is used to meet user needs, while the user experience is used as an assessment of the system designed. The target of My Pets application is for pet parents. It  has several stages; empathize, define, ideate, prototype, and testing. At the empathize stage it produces the main problems which are used as material for researchers to find a solution, problems obtained from the results of interviews and observations of 25 respondents. In the define stage, it begins to determine the problem as main focus to be solved. The ideate stage, it generates a solution to an existing problem. The prototype stage develops designs based on the previous stages. At the testing stage using the system usability scale to 25 respondents and getting a result of 87.7 or excellent. Based on the test results, My Pets application has been completed and assessed as effective based on the design thinking’s method. It is expected the design made can be used and the system developed better in the future